Klithih as an Expression of Adolescent Identity Crisis in Yogyakarta - Hidayat, Taufiq (Universitas Pahlawan Tuanku Tambusai, 2025)
The phenomenon of klithih in Yogyakarta has shifted in meaning from a neutral activity of wandering aimlessly to acts of random street violence committed by adolescents. This behavior not only disrupts public safety but also reflects an underlying identity crisis experienced by youth. According to Erik Erikson’s psychosocial development theory, adolescence is marked by the stage of identity vs. role confusion, a critical period for identity formation. Failure to navigate this stage successfully may lead to deviant behaviors. This study aims to understand adolescent involvement in klithih as a manifestation of unsuccessful identity development. Using a qualitative approach with a phenomenological perspective, the study explores psychosocial dynamics, social environmental influences, and the construction of meaning related to the self-identity of klithih perpetrators. The findings indicate that klithih serves as an expression of identity confusion, exacerbated by weak social support, a strong need for recognition, and peer group solidarity. These insights highlight the importance of psychosocial-based interventions and the reinforcement of family and educational roles in supporting adolescents’ identity formation processes.